G. Eric Matson and Edith Matson papers - Matson, G. Eric (Gästgifvar Eric), 1888-1977.; Matson, Edith
Correspondence, diaries, financial records, invoices, printed matter, maps, photographs, and other papers relating to chiefly to Matson's operation of the Matson Photo Service in California. Also documents his work as a photographer in Jerusalem with the American Colony Photo Dept. and conditions in Palestine. Correspondents include Louis George Deeb, Gabriel Said Diek, Joseph H. Giries, Lars E. Lind, Hanna Safieh, Michel S. Stephan, and Mattson (Matson also Matsson) family members.
Photographer.
Collection material in English and Swedish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Deeb, Louis George -- Correspondence; Diek, Gabriel Said -- Correspondence; Giries, Joseph H. -- Correspondence; Lind, Lars E., -- 1891- -- Correspondence; Safieh, Hanna, -- 1910-1979 -- Correspondence; Stephan, Michel S. -- Correspondence; Mattson family -- Correspondence; American Colony (Jerusalem). -- Photo Department; Matson Photo Service; Photography; Jerusalem -- Description and travel; Palestine -- Description and travel; Palestine -- History -- 20th century; Palestine -- Social conditions -- 20th century; Photographers